Multimodal neuroimaging investigation of post-stroke fatigue in middle-aged and older adults: combining resting-state fMRI and DTI-ALPS analysis - Sun, Jingjing; Tang, Yanlin; Wang, Wenni; Zhang, Yong; Ji, Hengshan; Wang, Peng (Frontiers in Aging Neuroscience, 2025)
BackgroundPost-stroke fatigue (PSF) is a prevalent but often overlooked complication, particularly in middle-aged and older stroke survivors. Neuroimaging studies exploring the neural mechanisms of PSF in this age group are limited. This study aimed to identify imaging markers for PSF in middle-aged and older adults using a multimodal imaging approach.MethodsThis retrospective case–control study analyzed data from patients with first ischemic stroke aged 50 years and above who were treated from January 2021 to June 2022 at the First Hospital of the University of Science and Technology of China. PSF was assessed using the Fatigue Severity Scale (FSS) and diagnostic criteria. All patients underwent resting-state functional MRI (rs-fMRI) and diffusion tensor imaging along perivascular space (DTI-ALPS) to assess brain functional connectivity and glymphatic system function.ResultsThe PSF group (mean age 62.7 ± 10.50 years) showed reduced global functional connectivity compared to non-fatigued controls (mean age 58.40 ± 9.20 years) (p < 0.05, FDR corrected), with enhanced connectivity between the insula and right inferior frontal gyrus. DTI-ALPS analysis revealed a negative correlation between DTI-ALPS index and fatigue severity (R2 = 0.40, p < 0.001) in the PSF group, suggesting an association between impaired glymphatic clearance and fatigue symptoms in middle-aged and older stroke survivors.ConclusionThis multimodal neuroimaging study highlights altered brain functional connectivity and glymphatic dysfunction as potential neural correlates of PSF in middle-aged and older adults. The findings provide novel insights into the complex pathophysiology of PSF in the aging brain, implicating both functional brain networks and the glymphatic system. Further research is warranted to validate these age-specific findings and explore targeted interventions for PSF in older stroke survivors.